Burned-Out Tumor of the Undescended Testis: A Rare Cause of Intra-Abdominal Mass in Childhood - Bakal, Unal; Onur, Mehmet Ruhi; Sarac, Mehmet; Tartar, Tugay; Kontas, Olgun; Kazez, Ahmet (Aves, 2018)
Germ cell tumors may manifest as a burned-out testis tumor in the abdomen that is characterized by lymph node metastasis or another manifestation of a metastatic neoplasm with a partially or totally histologically regressed, occult primary tumor in the testis. An 8-month-old boy presented with abdominal mass and hypospadias. On physical examination, a palpable abdominal mass in the left abdomen, the absence of the left testis in the scrotum, and hypospadias were found. Color flow Doppler ultrasonography revealed a well-defined, hypoechoic mass with no vascular flow. A laparoscopy was performed. No testis was found in the inguinal region and the abdomen. An amputated, smooth surface with brown color mass was found in the retrovesical area of the peritoneum. The mass was removed, and macroscopic examination of the lesion yielded a well-defined, stone hard mass. No live tissue was found histopathologically. Immunohistochemical studies revealed relatively positive findings for germ cell tumor. To our knowledge, this case report is the first burned-out germ cell tumor that developed in the undescended testis in children. Here, we present the clinical and imaging findings of a burned-out germ cell tumor of the undescended testis.
Keywords: Undescended testis; germ cell tumor; burned-out tumor; ultrasonography; magnetic resonance imaging